The Indispensable Nature of Persons with Intellectual Disabilities to the Church - McNair, Jeff (Journal of religion, disability & health, 2008)
In relation to 1 Corinthians 12: 22, why would persons with intellectual disabilities be indispensable to the Christian church? This article examines that question by looking at one core aspect of Christian faith, love. Discussion is then made as to how persons with cognitive and other disabilities contribute to the core aspect and what their absence may imply about the church and love as currently evidenced in the church.